Corelation Anemia Status With Learning Achievment Of The Second Level Under Graduate Students Of Dharma Husada Nursing Academy Kediri - Puguh Santoso (Akademi Keperawatan Dharma Husada Kediri, 2015)
experience by individuals. One of the internal factors that have a correlation with learning achievement is Another factor related with a physical condition that impairs the ability to learn, one of which is anemia. This research aim to analyze the correlation between anemia status on the sekond-level of undergraduate students of Dharma Husada Nursing Academy Kediri. Population of this research was the third-level of undergraduate student of Dharma Husada Nursing Kediri academic year of 2014 / 2015, which consists of two classes. Samples were taken using simple random sampling technique and found 91 subjects. Haemoglobin level data was obtained using cyanmethemoglobin measurement method and learning achievement data was obtained using learning documentation. Data were analyzed with bivariate tests using simple regression with a confidence level of 95% (α=5%). of the second-level undergraduate students of Dharma Husada Nursing Academy Kediri (p=0,014). achievement of the second-level undergraduate students of Dharma Husada Nursing Academy Kediri. Contribution anemia status on learning achievement were 2,9%, while 97,1% were related to another factor that were not analyzed in this research. Keywords: Students, Anemia Status, Learning Achievement